Liliopsida, Cyperaceae, Cephalocarpus confertus Gilly, Guyana Shield, Brazil, Colombia and Venezuela - Irene Fedón (Check List, 2011)
The genus Cephalocarpus (Cyperaceae), of South American distribution is represented by four species. The present work extends the distribution of Cephalocarpus cofertus Gilly based on analysis of samples from the Missouri Botanical Garden Herbarium, literature and online databases. As a result this species is reported for Brazil, Colombia and Venezuela and is removed from the endemic status for Venezuela.